ANALISIS FAKTOR YANG MEMENGARUHI KEJADIAN KECELAKAAN KERJA PADA BAGIAN HOT WORK DI PROYEK TOP GOLF PT.X TAHUN 2023 - Dina Nurseptiani (2024)
The construction sector has experienced extraordinary growth. The high risk of work often makes the construction sector the contributor to the highest number of work accidents. The aim of this research is to determine the factors that most influence the occurrence of work accidents among workers in the hot work section of the PT. This research method is quantitative analysis with a cross-sectional design. With a sample of 86 workers, the data was analyzed univariately to see a picture of each variable and multivariately using a multiple logistic regression test to find out which variables had the most influence on work accidents. The results of the analysis show that the variable use of PPE is the most influential factor with a POR value of 9.477, which means that workers who do not wear complete PPE have a 9.477 times greater risk of experiencing work accidents. It was also found that other variables had an influence on work accidents, namely age, overtime, K3 knowledge, K3 management, unsafe actions and unsafe conditions. Suggestions that can be given to companies are to increase supervision of K3 management, especially supervision of the use of PPE during work, and improve housekeeping